Improving Online Learning Effectiveness by Utilizing Learning Management System (LMS) to Support the Quality of Company Human Resources Improvements - Dakikotis Sururiyah; Gancar Candra Premananto (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This article aims to describe efforts to increase the effectiveness of the use of the Learning Management System (LMS) in improving learning outcomes and improving the quality of Human Resources (HR). The writing of this article uses the literature study method, namely reviewing and researching various literatures related to the topic of the problem being studied. The required data was collected through a contextual study which was then analyzed for its contents. The use of LMS in learning makes it easier for education and training management institutions to improve the learning process, learning can be accessed from various places and unlimited times, and learning can be carried out more simply. The use of LMS also makes learning more flexible in terms of study time and makes students more independent. Instructors can also monitor student activities through the LMS in detail.